2021
DOI: 10.3390/pathogens10070834
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Genomic and Pathogenic Features of the Potentially Zoonotic Streptococcus parasuis

Abstract: Recently, Streptococcus suis reference strains of serotype 20, 22, and 26 were reclassified as Streptococcus parasuis. The public health significance of S. parasuis is underestimated due to the lack of clinical isolates. In the present study, we first reported two sporadic S. parasuis infections in humans, after using full-length 16S rRNA and housekeeping genes’ phylogeny and ANI values of genome sequence comparisons to determine the species of their isolates BS26 and BS27. Compared to highly pathogenic S. sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…First, the species of these isolates were checked at the genomic level. The ANI and Tetra of one isolate, 2843, also named 2674 in a previous study [ 8 ] (recognised by the same Genbank number), are highly different from the other 14 S. parasuis isolates. Further, we analysed the genome composition and found that 79% genes (1736/2198) of this isolate are unique and the size core-genome has a huge reduction after adding this isolate to analyses (from 1043 to 264) (Additional file 5 ).…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…First, the species of these isolates were checked at the genomic level. The ANI and Tetra of one isolate, 2843, also named 2674 in a previous study [ 8 ] (recognised by the same Genbank number), are highly different from the other 14 S. parasuis isolates. Further, we analysed the genome composition and found that 79% genes (1736/2198) of this isolate are unique and the size core-genome has a huge reduction after adding this isolate to analyses (from 1043 to 264) (Additional file 5 ).…”
Section: Resultsmentioning
confidence: 76%
“…The CPS biosynthesis gene cluster drives the formation of streptococcal capsule of Streptococci . Previously Wang et al aligned the cps locus difference between S. parasuis and S. suis and found that there were frequent interspecies horizontal transfers between the cps locus of S. parasuis and S. suis , and verified that both S. parasuis and S. suis synthesised their CPS using the WZX/WZY pathway [ 8 ]. In this study, the intraspecies difference of S. parasuis was explored, and we found 11 different cps types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most S. parasuis strains have been isolated from the saliva of clinically healthy pigs, the presence of S. parasuis in diseased pigs and calves with pneumonia or systemic infection (meningitis, arthritis, endocarditis, or septicemia) indicates that this species may be pathogenic in pigs and calves [3][4][5][6]. In our previous study, two S. parasuis clinical strains, BS26 and BS27, were isolated from a patient with peritonitis and a patient with pneumonia and arthritis, respectively [7]. In the present study, a third S. parasuis clinical strain, NN1, was isolated from a patient with pneumonia.…”
Section: Introductionmentioning
confidence: 99%